2021
DOI: 10.3389/fped.2021.679546
|View full text |Cite
|
Sign up to set email alerts
|

Severe Retinopathy of Prematurity Is Not Independently Associated With Worse Neurodevelopmental Outcomes in Preterm Neonates

Abstract: Purpose: To evaluate the relationship between retinopathy of prematurity (ROP) severity and neurodevelopmental outcomes in premature neonates at 0–36 months corrected age.Methods: A retrospective chart review was performed on 228 neonates screened for ROP at the UCLA Mattel Children's Hospital between 2011 and 2018. Demographic information, clinical outcomes, ROP severity (no ROP, type 1 ROP, type 2 ROP), and Bayley-III neurodevelopmental scores were collected. Infants were grouped into corrected age cohorts (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Fifty-eight percentage of our cohort developed amblyopia. The incidence of amblyopia in patients with has previously been reported to be as high as 27.8% in type 1 ROP (22). Finally, 58% of our cohort also developed strabismus.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Fifty-eight percentage of our cohort developed amblyopia. The incidence of amblyopia in patients with has previously been reported to be as high as 27.8% in type 1 ROP (22). Finally, 58% of our cohort also developed strabismus.…”
Section: Discussionsupporting
confidence: 56%
“…ROP zone itself has been shown to be a risk factor for neurodevelopmental delay (33). On the other hand, the severity of ROP has not been shown to be associated with neurodevelopmental delay (22).…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome of CCS on BSID-III/IV was reported in five studies ( n = 922) at 18–24 months ( 26 , 28 , 34 , 35 , 44 ). The standard mean difference (SMD) was not different between the “no ROP” and “any ROP” groups (SMD: −0.820 to −2.43; p = 0.32; I 2 =98%).…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, developmental outcomes, including cognitive, language and motor functions, were similar between preterm infants with or without ROP and independent from ROP severity [ 96 ]. In line with these studies, Altendahl et al examined cognition, language, and motor scores of premature neonates at 0–36 months corrected age, screened for ROP, and found that ROP severity was not associated with worse neurodevelopmental scores [ 97 ]. Similar results were obtained in a recent study evaluating the presence of hearing loss in a large cohort of preterm infants at 18 months corrected age, revealing no significant associations between ROP and hearing impairments [ 98 ].…”
Section: The Impact Of Rop In the Central Nervous Systemmentioning
confidence: 99%